SI TENGGANG’S EFFORT IN FINDING CULTURAL IDENTITY DEPICTED IN MUHAMMAD HAJI SALLEH’S SI TENGGANG’S HOMECOMING - WARDANI, DWI SINTA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Wardani, Dwi Sinta. 2015. Si Tenggang’s Effort in Finding Cultural Identity Depicted in Muhammad Haji Salleh’s,  Si Tenggang’s Homecoming.  Study Program of English, Department of Languages and Literatures, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Arcci Tusita; Co-Supervisor: Fredy Nugroho Setiawan.  Keywords: cultural identity, post-colonialism, Si Tenggang’s Homecoming    In post-colonial era, binary opposition between West and East affects the mentality and identity the Eastern. For some occasions, the Easterners imitate the Western culture in order to have equality. It may lead to identity crisis in finding cultural identity. The process of finding cultural identity is depicted throughout in a poem written by Muhammad Haji Salleh entitled Si Tenggang’s Homecoming. In this poem, Salleh as the writer portrays how Si Tenggang, as  the figure of the poem adopts the new culture in the Western country when he studies abroad. Therefore, this study  investigates  the finding of cultural identity in Si Tenggang when  he  experiences  a cross cultural exchange with the Western culture  and adjustment process after his homecoming.  Post-colonial criticism  and other theories  proposed by Homi K. Bhabha,  namely  mimicry, hybridity and ambivalence and  the last post-colonial identity, a  theory proposed by Stuart Hall are used to analyze the material research.   The result of this research  shows Si Tenggang’s  adaptation in American culture and Si Tenggang’s re-establishment in Malaysian culture. Throughout this analysis, there are  differences between Si Tenggang’s journey and  his homecoming. During studying abroad, he learns many things about culture and variety  such as mimicking the new culture.  Thus, after  his homecoming Si Tenggang becomes a hybrid figure who is different from common Malaysian. He becomes wiser and mature. Consequently, people in his native country questions his identity as Malay. At that time, he is ambivalent. Yet, after convincing himself and his society in the native country, he is sure with his identity as hybrid figure and positioning himself at the Third Space.  It is concluded that cross cultural exchange has influenced cultural identity in Si Tenggang.    The following researcher is  suggested to explore Si Tenggang’s experiences by using biographical approach. It is aimed to examine the correlation between the poem with the author’s life.